Terapi Komplementer The Effect Of Swedish Massage Complementary Therapy On Lowering Blood Pressure In Pregnant Women - Dina Arianty; Laurensia Yunita; Nur Hidayah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hypertension is a health problem that is very common in society, can be found in adulthood. This disease is usually undetected and does not cause typical symptoms for sufferers, therefore this disease can be called the